(untitled) (Bangladesh Journal of Infectious Diseases, 2018)
Background: Obesity, characterized by increased fat mass and is currently regarded as a proinflammatory state and frequently associated with increased risk of cardiovascular diseases including Myocardial Infarction and also future risk for development of metabolic disorders such as T2DM. Highsensitivity C-reactive protein is a well-known inflammatory marker. Objective: In this study we aimed to determine the levels of serum high-sensitive C-reactive protein in obese parsons with normal glucose tolerance (NGT) and obese with impaired fasting glucose (IFG) individuals. Methodology: This was a case-control study which was conducted in the Department of Biochemistry, ZH Sikder Women’s Medical College, Dhaka during the period of July 2014 to June 2015. The age, sex and body mass index (BMI ≥ 30 kg / m²) matched 25 obese subjects with NGT were selected as control group and 25 obese patients with IFG were selected as case group. We measured levels of serum high sensitive Creactive protein in all groups. Subjects of both obese groups had significantly higher hs-CRP levels than the normal range. Results: A total number of 50 subjects were recruited for this study of which 25 obese subjects with NGT were selected as control group and 25 obese patients with IFG were selected as case group. The level of hs-CRP in obese with NGT and with IFG were found 2.91±1.56 mg/L & 3.42±1.72 mg/L, respectively. There are no significant difference between hs-CRP levels of obese subjects than the subjects with IFG (p>0.1). Conclusion: This study finding has concluded that obesity raises serum hsCRP level. IFG obese individuals are not at much higher cardiovascular and metabolic risk level than normal obese parsons. Bangladesh Journal of Infectious Diseases 2017;4(1):21-24